Characterization of hydroxylated hyperbranched polyesters of fourth and fifth generation (2010)
ABSTRACT: Hydroxylated hyperbranched polyester (HBPs) of fourth and fifth generation were obtained by three methods; one step (HBP4, HBP5), step by step (HBP4P, HBP5P) and combinations of one step and step by step (HBP1-4, HBP1- 5). The HBPs were synthesized in bulk from 2,2-bis(hydroxymethyl)propionic acid (DMPA) and pentaerythritol (PE) using acid catalysis (p-toluenesulfonic acid) and characterized by infrared analysis, 1H and 13C nuclear magnetic resonance, gel permeation chromatography, vapor pressure osmometry, electro spray ionizationmass spectrometry, dynamic light scattering, refractive index, thermogravimetric and differential scanning calorimetric analysis. The refractive index of HBPs were low, the infrared and nuclear magnetic resonance analysis showed evidence of the occurrence of reaction between from 2,2-bis(hydroxymethyl) propionic acid (DMPA) and pentaerythritol (PE). The molar mass values of the HBPs determined by gel permeation chromatography were different to vapor pressure osmometry measurements due to small hydrodynamic volume of the HBPs. The mass spectrometry analysis showed different acyclic and cyclic units in the HBPs. The distributions of HBPs studied by dynamic light scattering were monomodal in number and volume and bimodal in intensity. The thermal stability of the fifth generation HBPs was higher than that the fourth generation. All HBPs presented amorphous behavior.